(untitled) (Journal of Applied Learning and Teaching, 2023)
The high-calibre education in Australia has attracted overseas students to pursue a Higher Degree by Research (HDR) every year. While HDR training is crucial for all HDR students, international students are relatively vulnerable due to the challenging demands of academic writing and research, coupled with the cultural and language barriers different from their own. To worsen the situation, the global pandemic forced face-to-face supervision into remote supervision mode, thus exacerbating students’ social-emotional learning state even further. This article transports readers to a telecollaborative project that I initiated amid the pandemic through an autoethnographic approach. Propelled by the urgent need to better support supervisees beyond boundaries, I enacted a transnational telecollaboration to mentor international HDR students to position themselves as emerging researchers. Informed by participatory action research (PAR), I guided my junior colleagues (early career researchers (ECRs)) to conduct HDR needs analysis, hold HDR training webinars, build a virtual community via Facebook, and shadow HDR students throughout their reflection journaling via Google Docs. This viable supervision model broke down the power structure by creating an ecologically balanced framework, thus promoting collaboration rather than isolation.